GENESIS OF ART AND INDUSTRIAL SCHOOLS IN GALICIA (END OF 19th CENTURY – 1918): HISTORICAL AND PEDAGOGICAL ASPECTS - Ivaniuk, Hanna (Mountain School of Ukrainian Carpaty, 2021)
The article highlights the results of a study of the current scientific problem of the genesis of art and industrial schools in Galicia during the history of the late 19th century - 1918. Within these chronological boundaries, Galicia developed in the legal field of the Austro-Hungarian state. The genesis of art and industrial schools in Galicia is a cultural and educational phenomenon - the connection of traditional practices of folk-art culture and European aesthetic concepts and practices. The influence of the state economic and educational policy on the formation of art and industrial schools in Galicia, which was in the status of the Crown Land, and later - the Crown Land of the Austro-Hungarian Monarchy, is revealed. According to the results of historical and pedagogical research, the cooperation of art museums operating in Austria-Hungary and other European countries, their cultural and educational mission in the development of art and industrial schools in Galicia in the political and legal field of the Austro-Hungarian monarchy. The purpose is achieved: the peculiarities of formation and development of art and industrial schools in the lands of Galicia as a cultural-educational phenomenon of progress within the specified chronological limits are substantiated and generalized. According to the results of the analysis of theoretical and archival sources, the preconditions and peculiarities of the formation and development of art and industrial schools in Galicia in these years are highlighted. The factual material presented in the article can serve to summarize new knowledge about the historical post of schooling in Galicia.